Projected incidence trends of need for long-term care in German men and women from 2011 to 2021 - Voß, Sabrina; Knippschild, Stephanie; Haß, Luisa; Tönnies, Thaddäus; Brinks, Ralph (Frontiers in Epidemiology, 2023)
Background: The German Federal Statistical Office collects and reports aggregated numbers of people in need for long-term care (NLTC) stratified by age and sex routinely. Age-and sex-specific prevalence of NLTC from 2011 to 2021 is reported as well. One estimation of the incidence rate of NLTC based on the age-and sex-specific prevalence that did not explore possible trends in incidence (based on MRR (mortality rate ratio)), which is important for an adequate projection of the future number of people with NLTC, exists.Objective: We aim to explore possible trends in age-specific incidence of NLTC in German men and women from 2011 to 2021 based on different scenarios about excess mortality (in terms of MRR) Methods: Incidence of NLTC was calculated based on an illness-death model and a related partial differential equation based on data from the Federal Statistical Office. Estimation of annual percent change (APC) of the incidence rate was conducted in 8 scenarios.Results: There are consistent indications for trends in incidence for men and women aged 50-79 years with APC in incidence rate of more than +9% per year (up to nearly 19%). For ages 80+ the APC is between +0.4% and +12.5%. In all scenarios, women had higher age-specific APCs than men.We performed the first analysis of APC in the age-and sex-specific incidence rate of NLTC in Germany and revealed an increasing trend in the incidences. With these findings future prevalence of NLTC can be estimated that may exceed current prognoses.